BALDONE 1.2M TELESCOPE PLATE ARCHIVE - HIDDEN RESERVES OF THE FON PROJECT - Eglitis, I.; Eglite, V.; Andruk, V.; Protsyuk, Yu.; Protsyuk, S.; Kovylianska, O. (Одеські астрономічні публікації, 2018)
The plate archive of the 1.2 m Baldone telescope (Latvia) has approximately 780 and 4660 astronegatives exposed in 1967-1993 in the U (ZU21 + UG1 filter plates) and V (A600N + ZS17 filter films) closed to Johnson system U and V passbands. Digitization of astronegatives is carried out using the Epson Expression 10000XL scanner, the scanning mode is 1200 or 2400 dpi, each field covers 19 square degrees of sky. The plates and films are scanned at the Baldone Observatory, processing of digitized scans is carried out by the observers in Baldone, at the Research Institute "Mykolaiv Astronomical Observatory" and at the Main Astronomical Observatory of the National Academy of Sciences of Ukraine. The Epson Expression 10000XL Scanner, along with the software developed, allows us to digitize and process the plates and receive coordinates and magnitudes of registered objects (with high, moderate and low brightness) with an internal error of no worse than 0.05 seconds of arc and 0.03 magnitude. The astrometric and photometric reduction of digitized astronegatives is done in the Tycho-2 reference system and U, V photoelectric system. At this report, we present first results of reduction of more than 2000 astronegatives. Data of U and V magnitudes of stars and galaxies will be used as the photometric addition to the FON project, without, the long-term series of U, V observations have an independent value for studying the variability of stars. Also, many plates included open clusters and will be used for investigation of their population and photometric parallaxes.